89=-43+x

Simple and best practice solution for 89=-43+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 89=-43+x equation:



89=-43+x
We move all terms to the left:
89-(-43+x)=0
We add all the numbers together, and all the variables
-(x-43)+89=0
We get rid of parentheses
-x+43+89=0
We add all the numbers together, and all the variables
-1x+132=0
We move all terms containing x to the left, all other terms to the right
-x=-132
x=-132/-1
x=+132

See similar equations:

| -3+2x=10×+21 | | 10x^2-34x-33=0 | | 30-2y-2y=10 | | 3+5x-4=5x+1 | | (2x-1)(x+2)^2=0 | | 97x-37x3=3x-15 | | -3/19+5y=7 | | 7x-11=x+31 | | -3.8-3x=4.0 | | 4(32-7)=65-3(4z-9) | | 3(2x-1)=8x+4-x | | 2x-7=7x2 | | 2/3z+1=1 | | 10p^2-18p+68=0 | | 3x+6=4(x-2)+1 | | 10p^2-9p+34=0 | | 6x+32=44 | | -325+x=77 | | 57=2x+(2x-3)+x | | 88=x-106 | | 144+x=144 | | 0=18x-9x | | -27+15x=-132 | | 135=x-420 | | 11=x-110 | | N^2+n-62=0 | | 2(h+1)=0 | | 2(h+1)=(h+1)(h+1) | | N^2+n-58=0 | | 6c+3=-4c-2 | | 150.25x=225.75 | | 3y^2-4y+2=0 |

Equations solver categories